First report of root-knot nematode \(Meloidogyne enterolobii \) infecting pomelo (\(Citrus maxima\) (Burm.) Merri) in Vietnam - Linh Le, Thi Mai; Tien Nguyen, Huu; Duyen Nguyen, Thi; Son Nguyen, Giang; Phap Trinh, Quang (Academia Journal of Biology, 2023)
Meloidogyne enterolobii Yang & Eisenback, 1983 is amongst the most aggressive root-knot nematodes, causing significant annual losses worldwide to many crops and emerging in many countries recently. Although plants belonging to the citrus family such as grapefruit and citrus have been reported as non-hosts or poor hosts for M. enterolobii, our study recorded the heavy infection of a root-knot nematode that resembles M. enterolobii on pomelo, a species in the citrus family. The molecular data of D2-D3 of 28S rRNA region, morphometrics, and morphological features of second-stage juveniles, males, and females in the present study have confirmed that the root-knot nematode recovered from pomelo in Vietnam belongs to M. enterolobii. To the best of our knowledge, this represents the first report of M. enterolobii infecting pomelo, providing new insight into the host status of this important pest.